Analisis Pengaruh Kebijakan Akuntansi pada Kualitas Pelaporan Keuangan Perusahaan Terbuka di Indonesia - Adrin Pilua; Asih Anggriani S. Dg. Cennu; Gerry Cristyo Dalim (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
This study aims to analyze the effect of accounting policies on the quality of financial reporting of listed companies in Indonesia, with company size as a control variable. In this context, accounting policies refer to the rules and procedures applied by companies in preparing financial statements, while financial reporting quality includes the accuracy, completeness, and transparency of the information presented. This study uses panel data from five companies listed on the Indonesia Stock Exchange during the period 2018 to 2023. The analysis method used is multiple linear regression with t test and F test to test the research hypothesis. The results showed that accounting policies have a significant effect on the quality of the company's financial reporting, while company size has no significant effect.